2015
DOI: 10.3341/jkos.2015.56.9.1331
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Diffractive Trifocal Intraocular Lens in Both Eyes: A 6-Month Follow-Up

Abstract: Purpose:To evaluate clinical outcomes after cataract surgery with bilateral implantation of the diffractive trifocal intraocular lens (IOL). Methods: Forty-four eyes of 22 patients were analyzed in the present study from July 2014 to December 2014. Phacoemulsification with bilateral implantation of an AT Lisa tri 839 MP IOL (Carl Zeiss Meditec, Jena, Germany) was performed. Over a 6-month follow-up, the main outcome measures were uncorrected distance visual acuity (UDVA), uncorrected intermediate visual acuity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In a large multicenter trial conducted in western countries, binocular UCIVA and UCNVA was better for subjects who received TFNT00 compared with those who received AT LISA tri 839MP ( P = 0.002 and P = 0.003, respectively) 6 months after IOL implantation [ 16 ]. Recent trials of the AT LISA tri 839MP IOL, which has an intermediate focal point at 80 cm, in Korean subjects showed that AT LISA tri 839MP provided better VA at intermediate distances compared with a conventional multifocal IOL [ 27 ]; however, UCIVA was 0.13 logMAR 6 months after implantation of AT LISA tri 839MP [ 28 ]. Although future comparative studies should be conducted for Asian populations, the results of the current study indicate that visual outcomes may be improved with TFNT00 compared with AT LISA tri 839MP for subjects in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…In a large multicenter trial conducted in western countries, binocular UCIVA and UCNVA was better for subjects who received TFNT00 compared with those who received AT LISA tri 839MP ( P = 0.002 and P = 0.003, respectively) 6 months after IOL implantation [ 16 ]. Recent trials of the AT LISA tri 839MP IOL, which has an intermediate focal point at 80 cm, in Korean subjects showed that AT LISA tri 839MP provided better VA at intermediate distances compared with a conventional multifocal IOL [ 27 ]; however, UCIVA was 0.13 logMAR 6 months after implantation of AT LISA tri 839MP [ 28 ]. Although future comparative studies should be conducted for Asian populations, the results of the current study indicate that visual outcomes may be improved with TFNT00 compared with AT LISA tri 839MP for subjects in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…The monocular visual outcomes of our study were comparable with the results of previous studies. In an investigation of a Korean population, Kwon et al [ 16 ] reported clinical outcomes of other commercially available trifocal IOLs (AT LISA tri 839 MP) with 6-month postoperative UDVA, UIVA, and UNVA values of 0.00, 0.13, and 0.15 logMAR, respectively. Our visual outcomes were comparable to those of Kwon et al [ 16 ] and slightly better for the UNVA.…”
Section: Discussionmentioning
confidence: 99%